Liability Insurance as a Method of Risk Management in Clinical Trials Medical Products - Piechota, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
According to polish legislation, regulations concerning clinical trials are different for therapeutic products than for medical products, equipment of the medical device or active implantable medical devices.This article discusses the regulations concerning the registration of medicines, particularly the civil liability of the researcher's and the sponsor's responsibility in case of conducting the clinical trials of the therapeutic product.Also, there are presented the risks and threats for the agents involved in the clinical trial, including the clinical trial participant, as this person takes the risk for unwanted of medical product intake.